(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
The purpose of this article is to establish the different forms of psychological violence that occur in a relationship, from courtship to marriage, although silent and without leaving traces on the skin, it is one of the most painful forms of violence. In this regard, psychologist Lenore Walker (1984) defines psychological violence as a set of behaviors and attitudes aimed at controlling, dominating, manipulating and humiliating the partner through the use of intimidation, fear, shame, guilt and denial. Regarding the method, it belongs to the mixed approach with non-experimental design. Regarding the type of research, it is documentary with descriptive scope. Regarding the data collection technique, it is based on documentary analysis, both of the literature, as well as the cases filed in the Criminal Unit No. 1 of the Zonal Prosecutor’s Office of the city of Presidente Franco, in the period of time from 2020 to 2022. This study concludes that different forms of psychological violence are still normalized in cohabitation relationships and are associated with the consumption of alcoholic drinks.